2022
DOI: 10.1021/acs.jpclett.2c01652
|View full text |Cite
|
Sign up to set email alerts
|

Static Disorder in Lead Halide Perovskites

Abstract: In crystalline and amorphous semiconductors, the temperature-dependent Urbach energy can be determined from the inverse slope of the logarithm of the absorption spectrum and reflects the static and dynamic energetic disorder. Using recent advances in the sensitivity of photocurrent spectroscopy methods, we elucidate the temperature-dependent Urbach energy in lead halide perovskites containing different numbers of cation components. We find Urbach energies at room temperature to be 13.0 ± 1.0, 13.2 ± 1.0, and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
39
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 41 publications
6
39
1
Order By: Relevance
“…The fitting of the model to the experimental data gives that 𝐸 𝑝ℎ = 20 ± 2 𝑚𝑒𝑉, which is within the same order of magnitude of the value calculated for LO phonons using the Segall's expression. On the other hand, 𝐸 𝑈 (0) = 8 ± 2𝑚𝑒𝑉 which is very close to the results in thin films of different composition recently reported 67,96,98 , although a bit higher as expected for nanoparticles. In the work by Zeiske and collaborators it is also argued that the very low values for 𝐸 𝑈 (0) obtained in perovskites are produced by the excellent quality of the crystal structure and that the static contributions to Urbach energy are dominated by zero-point phonon energy.…”
Section: 3urbach Tail and Structural Disordersupporting
confidence: 90%
See 3 more Smart Citations
“…The fitting of the model to the experimental data gives that 𝐸 𝑝ℎ = 20 ± 2 𝑚𝑒𝑉, which is within the same order of magnitude of the value calculated for LO phonons using the Segall's expression. On the other hand, 𝐸 𝑈 (0) = 8 ± 2𝑚𝑒𝑉 which is very close to the results in thin films of different composition recently reported 67,96,98 , although a bit higher as expected for nanoparticles. In the work by Zeiske and collaborators it is also argued that the very low values for 𝐸 𝑈 (0) obtained in perovskites are produced by the excellent quality of the crystal structure and that the static contributions to Urbach energy are dominated by zero-point phonon energy.…”
Section: 3urbach Tail and Structural Disordersupporting
confidence: 90%
“…𝐸 𝑈 monotonically increases from 7 meV at 10 K to 21 meV at 290 K as shown in Figure 6 b, which is a consequence of an increased carrier-phonon interaction 96 . This behavior can be modeled using equation (9) 96,97 𝐸 𝑈 (𝑇) = 𝐸 𝑈 (0) coth ( 𝐸 𝑝ℎ 2𝑘 𝐵 𝑇 )…”
Section: 3urbach Tail and Structural Disordermentioning
confidence: 81%
See 2 more Smart Citations
“…Figure d shows the extracted Urbach energies: they are in broad agreement with previously reported values in the literature. ,, The values of the measured Urbach energies are all above 10 meV, much larger than our modeled values. This discrepancy has been attributed to the strong temperature dependent contribution to the Urbach energy that has been previously noted and assigned to dynamic disorder due to thermal occupancy of vibrational modes. , Some studies using temperature dependent photoluminescence measurements have indicated that extrapolation to low temperatures takes the Urbach energies down to a few meV . We note that our direct measurements of optical absorption are performed at room temperature, and we emphasize that our computational model introduces disorder only through the compositional alloying of the halides.…”
mentioning
confidence: 67%